Knowledge Networks in the Mekong - Clayton, T.E. (CGIAR Research Program on Water, Land and Ecosystems, 2018)
Knowledge networks, then and now, global or local, are meant to manage knowledge. This report examines knowledge networks in Southeast Asia's Mekong region. Water Knowledge is intended as an informal research output focusing on current research discussions and debates around the waters and rivers of Cambodia, Laos, Myanmar, Thailand, Vietnam and the Yunnan Province of China. Water Knowledge is not peer reviewed.